2006
DOI: 10.1093/nar/gkl527
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a high-affinity methyl-CpG-binding protein

Abstract: Core members of the MBD protein family (MeCP2, MBD1, MBD2 and MBD4) share a methyl-CpG-binding domain that has a specific affinity for methylated CpG sites in double-stranded DNA. By multimerizing the MDB domain of Mbd1, we engineered a poly-MBD protein that displays methyl-CpG-specific binding in vitro with a dissociation constant that is >50-fold higher than that of a monomeric MBD. Poly-MBD proteins also localize to methylated foci in cells and can deliver a functional domain to reporter constructs in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 27 publications
4
72
0
Order By: Relevance
“…Because MBD2 has a methyl-CpG binding domain, we tested to what extent MBD2 binding to DNA is dependent on methylation. To this end, we performed a methylated DNA precipitation on chip (MAP-chip), using a recombinant protein (4xMBD) consisting of four methyl-CpG binding domains derived from MBD1 31 to selectively precipitate methylated sequences. MAP is a highly specific and sensitive technique for selecting methylated other factors, and may thus play a dual role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because MBD2 has a methyl-CpG binding domain, we tested to what extent MBD2 binding to DNA is dependent on methylation. To this end, we performed a methylated DNA precipitation on chip (MAP-chip), using a recombinant protein (4xMBD) consisting of four methyl-CpG binding domains derived from MBD1 31 to selectively precipitate methylated sequences. MAP is a highly specific and sensitive technique for selecting methylated other factors, and may thus play a dual role.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids pET-4xMBD and pET-4xMBD-R22A, encoding respectively the recombinant wild-type His 6 -tagged 4xMBD and mutant His 6 -tagged 4xMBD-R22A in a bacterial system, were kindly provided by Dr. A. Bird. 31 Both recombinant proteins were purified from induced E. coli Rosetta (DE3 pLysS) cultures on Ni-NTA agarose (Qiagen, Courtaboeuf, were quantitated by Q-PCR. These were the BRCA1, 14 hTERT, 15 pS2, 29 PARVG, 18 RASSF1A 18 and GAPDH promoters.…”
Section: Methodsmentioning
confidence: 99%
“…Because AtMBD7 is unique in having three MBD motifs, we tested the significance of this feature for localization and binding affinity to its chromosomal sites. Recently, it has been shown that a recombinant poly-MBD protein made of the MBD motif of the mammalian Mbd1 has higher binding affinity to mCpG sites than the monomeric Mbd1 protein (10). This finding suggested that the naturally occurring poly-MBD protein AtMBD7 might display higher binding affinity for methylated sites than the monomeric AtMBD5 and AtMBD6 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules were selected from a mixture that included unmethylated DNA and were recognized using a fluorescently labeled methyl binding domain protein-1 (MBD1) that binds specifically to double-stranded, methylated DNA (24). We discuss the technologies that enabled us to identify methylated DNA bound with MBD1 using its fluorescence signature.…”
mentioning
confidence: 99%